Elevated atmospheric CO2 adversely affects a dung beetle's development: Another potential driver of decline in insect numbers?. (26th July 2021) - Tocco, Claudia; Foster, James; Venter, Nic; Cowie, Blair; Marlin, Danica; Byrne, Marcus
Abstract: Insect declines have been attributed to several drivers such as habitat loss, climate change, invasive alien species and insecticides. However, in the global context, these effects remain patchy, whereas insect losses appear to be consistent worldwide. Increases in atmospheric CO2 concentrations are known to have indirect effects on herbivorous insects, but the effects on other insects are largely unexplored. We wondered if elevated atmospheric CO2 (eCO2 ) could influence the growth and survival of insects, not via rising temperature, nor through their changes in food quality, but by other means. Rearing tunnelling dung beetle Euoniticellus intermedius (Reiche, 1848) at pre‐industrial (250 parts per million [ppm]), current (400 ppm) and eCO2 levels (600 and 800 ppm), we found that exposure to eCO2 resulted in longer developmental times and increased mortality. Elevated CO2 also caused reduction of adult size and mass which is detrimental to dung beetle fitness. Additional results showed associated increases in CO2 levels inside dung brood balls, dung pH and respiration rates of the soil surrounding the developing dung beetles (CO2 flux). We thus hypothesize that elevated CO2 increases competition for O2 and nutrients between soil microbiota and subterranean insects. Given that many insect orders spend at least part of their life underground, our findings indicate the possibility of a negative ubiquitous effect of eCO2 on a large portion of the earth's insect biota. These findings therefore suggest an important area for future research on the soil community in the context of atmospheric change. Abstract : In the context of global insect declines, we wondered if elevated atmospheric CO2 (eCO2 ) could affect insects, not via rising temperature, nor changes in food quality, but other means. A tunnelling dung beetle reared under eCO2 showed reduction in adult size and survival, along with longer developmental time. In addition, CO2 levels inside beetle brood balls, brood ball pH and CO2 flux in the surrounding soil increased under eCO2 . Given that many insect orders spend part of their lifecycle underground, this negative effect of eCO2 on a tunnelling insect might be a ubiquitous explanation for the decline in insect numbers.